Facile Synthesis of ZIF-67 for the Adsorption of Methyl Green from Wastewater: Integrating Molecular Models and Experimental Evidence to Comprehend the Removal Mechanism - Muniba Ikram; Sadaf Mutahir; Muhammad Humayun; Muhammad Asim Khan; Jehan Y. Al-Humaidi; Moamen S. Refat; Amr S. Abouzied (Molecules, 2022)
Organic dyes with enduring colors which are malodorous are a significant source of environmental deterioration due to their virulent effects on aquatic life and lethal carcinogenic effects on living organisms. In this study, the adsorption of methyl green (MG), a cationic dye, was achieved by using ZIF-67, which has been deemed an effective adsorbent for the removal of contaminants from wastewater. The characterization of ZIF-67 was done by FTIR, XRD, and SEM analysis. The adsorption mechanism and characteristics were investigated with the help of control batch experiments and theoretical studies. The systematical kinetic studies and isotherms were sanctioned with a pseudo-second-order model and a Langmuir model (R2 = 0.9951), confirming the chemisorption and monolayer interaction process, respectively. The maximum removal capacities of ZIF-67 for MG was 96% at pH = 11 and T = 25 °C. DFT calculations were done to predict the active sites in MG by molecular electrostatic potential (MEP). Furthermore, both Molecular dynamics and Monte Carlo simulations were also used to study the adsorption mechanism.